Dipole induced transparency and Aulter–Townes splitting via a dipole emitter coupled to a hybrid photonic-plasmonic resonator. (3rd September 2018) - Liu, Wenxiao; Wang, Xin; Luo, Mengmeng; Sun, Xuejian; Gao, Shaoyan; Li, Fuli
Abstract: We theoretically investigate the transmission characteristics of a probe field by coupling a dipole emitter to a hybrid photonic-plasmonic structure, which consists of a metal nanoparticle (MNP) and a whispering-gallery-mode microcavity. It is found that the coupling strength between the cavity and the dipole emitter can be significantly enhanced when the emitter is located in the vicinity of the MNP suface. Moreover, the Rayleigh scattering induced by the MNP enlarges mode broadening with increasing the MNP radius. The dipole induced transparency (DIT) and Aulter–Townes splitting (ATS) can both be observed in this system. These two phenomena are attributed to the competition between the local field enhancement and the associated interaction broadening. In addition, we have obtained the conditions for realizing DIT and ATS and present them in a phase diagram dependent on the geometric parameters (for example, the MNP radius and the distance between the surface of the MNP and the dipole emitter). By tuning the geometric parameters, we demonstrate a transition from DIT to ATS. The proposal can provide a platform for the study of nonlinear quantum optics and have applications in high-efficiency photon turnstile.